1984
DOI: 10.1111/j.1432-1033.1984.tb08535.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of an octadecapeptide with the biological and immunological properties of human heat-stable Escherichia coli enterotoxin

Abstract: An eighteen-amino-acid peptide having the linear amino acid sequence of human heat-stable enterotoxin (ST) has been synthesized by solid phase peptide synthesis. The purified peptide could be obtained in yields approaching 25% after purification by size, charge, and high-performance ligand chromatography. This material was pure and identical to native ST by analytical high-performance ligand chromatography, amino acid analysis, paper electrophoresis and thin-layer chromatography. The formation of the disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…With the relatively stable conotoxin GI, partial reduction by NaBH, in the presence of iodoacetic acid gave unambiguous results (Gray et al, 1984), although some exchange was detected. On the other hand, alkylation of partially oxidized enterotoxin led to incorrect assignments (Houghten et al, 1984). The present work describes a way to circumvent the exchange problem, opening a new route to disulfide assignment.…”
Section: Discussionmentioning
confidence: 92%
“…With the relatively stable conotoxin GI, partial reduction by NaBH, in the presence of iodoacetic acid gave unambiguous results (Gray et al, 1984), although some exchange was detected. On the other hand, alkylation of partially oxidized enterotoxin led to incorrect assignments (Houghten et al, 1984). The present work describes a way to circumvent the exchange problem, opening a new route to disulfide assignment.…”
Section: Discussionmentioning
confidence: 92%
“…Although it has been suggested that STa needs to retain some toxicity in order to become immunogenic when carried by a carrier protein (3,35,36), other studies clearly indicated that nontoxic STa antigens in fusion formats elicited neutralizing antibodies (18,19,20,28,46). It was demonstrated that synthetic mutated pSTa (pSTa N11P , pSTa Y18N ), when chemically cross-linked to an LT B subunit or porcine IgG molecules, elicited anti-STa antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that synthetic mutated pSTa (pSTa N11P , pSTa Y18N ), when chemically cross-linked to an LT B subunit or porcine IgG molecules, elicited anti-STa antibodies. Moreover, these anti-STa antibodies provided protection against ETEC infection (18,19,20). Data from the present study further confirm that the STa 13 toxoid, when fused to a carrier protein, elicits neutralizing anti-STa antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the synthetic ST toxin used by Klipstein and colleagues was based on the STp sequence published by Chan and Giannella (5), which was later discovered to have two interchanged residues (STp, Asn11Tyr and Tyr18Asn) (54). However, this mutant ST peptide apparently had the same biological and immunological properties as native ST (16,27). In spite of the apparent successful generation of both a chemical conjugate and a synthetic ST vaccine candidate, these promising studies have not been further pursued.…”
Section: St Vaccinologymentioning
confidence: 99%